Pengembangan Bahan Ajar Menulis Cerita Pendek dengan Pendekatan Kontekstual Berbasis Kearifan Lokal pada Siswa Kelas XI SMK - Arif Mazhuri Saputro; M. Bahri Arifin; Asnan Hefni (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2021)
This research aims to produce teaching materials, describing the feasibility and effectiveness of teaching materials writing short stories with a contextual approach based on local wisdom in XI grade students of SMK Negeri 1 Kota Bangun. This research is a model of research and development. The data sources in this study are obtained from the development, implementation of learning, quality of products of development results, material development process, and material preparation. Data analysis techniques include measuring student writing test results, student response measurement, validation and planning assessment. This research resulted in teaching materials to write short stories with a contextual approach based on local wisdom for vocational class XI students. The feasibility of teaching materials is obtained from validation results by language experts (93.75%). The media experts (88%) category is very feasible with ready-to-use product decisions in the field without revision. The effectiveness of teaching materials can be seen from the results of the observer assessment, which is 3.65 classified very well. Furthermore, the teacher response calculation was 96.73%, and the student response was obtained at 88.94%, classified as very feasible with ready-to-use product decisions in the field without revision. The short story writing test results yielded an average score of 85.9%, included in the excellent category. Test results write short stories on background aspects (100%), themes (97.5%) and language usage (90.83%) fall into the category very well. Thus, teaching books writing short stories with a contextual approach based on local wisdom can be used in the learning process for vocational students in XI grade.